The operation of infimal/supremal convolution in mathematical economics. Issue 5 (3rd May 2016) - Bayón, L.; García-Nieto, P.J.; García-Rubio, R.; Grau, J.M.; Ruiz, M.M.; Suárez, P.M.
Abstract : The infimal convolution operation arises in mathematical economics in the analysis of several problems. In this paper we first present a survey and summarize two previous papers by the authors on the classic firm's cost-minimization problem. Moreover, we present a new application: the analytical solution of the utility maximization problem which we shall obtain applying the supremal convolution operation.